2016
DOI: 10.4103/2152-7806.177896
|View full text |Cite
|
Sign up to set email alerts
|

Angiolymphoid hyperplasia with eosinophilia and entrapment of the ulnar nerve

Abstract: Background:The angiolymphoid hyperplasia with eosinophilia (ALHE) is a sporadic vasoproliferative lesion of uncertain etiology involving the skin and the subcutaneous tissue. Occasionally, it involves also the large arteries compressing the near nerves. ALHE is commonly confused with Kimura's disease because of their clinical and histological similarities.Case Description:We report a case of a 52-year-old female suffering from a 6-month pain and paresthesias in the fourth and fifth finger of the right hand. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our review of the literature revealed 24 well documented cases [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] . We did not include cases with poor documentation [27] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review of the literature revealed 24 well documented cases [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] . We did not include cases with poor documentation [27] .…”
Section: Discussionmentioning
confidence: 99%
“…The ALHE lesion in our patient involved the common digital artery and there were two other previously reported cases with common digital artery involvement [1] , [23] . Involvement of the radial artery [10] , [20] , ulnar artery [8] , [9] , [14] , brachial artery [2] , [11] , and axillary artery [12] , [13] have also been reported. Total excision of the involved artery is curative; and reconstruction with vein grafts is only mandatory after axillary and brachial artery excisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation